15 To improve the quality of e-discharge summaries for patients potentially in their last 12 months of life using the G.R.E.A.T tool. (14th March 2023) - Seelan, Bavan; Butler, Andrew; Burney, Syed; Alam, Johra; Downes, Rea; Avorgbedor, Shanthini; Abarshi, Ebun
Abstract : Introduction: Concise e-discharge summaries undoubtedly support seamless transition to enable clear treatment plans and ensure that patient preferences considered wherever possible. 'Ambitions-for-Palliative-and-End-of-Life-Care' national guidelines emphasise the importance of well-coordinated care; a concise summary will enable this ambition to be fulfilled. Now, discharge summaries fall under the purview of the medical team and serve as primary documents for communicating a patient's care plan between settings. While sifting through patient records, doctors need to know which information to include, to ensure excellent follow-up. Setting: Margaret Centre (MC) is an 11-bed specialist inpatient palliative care unit. In its 2021/22 annual report, 1 in 3 of all admissions were discharged to the community. The centre's vision is to provide 'specialist services without walls', achievable through healthy partnerships and collaborations at various levels. Method: As part of the Gold standard formwork, we examined e-discharge summaries for all discharges from 1 st January to 30 th September 2022. We used the G.R.E.A.T tool, adapted from Dudley Group NHS. G.R.E.A.T is an acronym for G- GSF Code; R- resuscitation status; E- End-of-life care (EOLC) medications; A-Advance Care Planning (ACP)including the Urgent Care Plan (previously Coordinate-My-Care; and T – treatment escalation plan (TEP). Results: Patients aged 60–102years. 20 males. All potentially within their last 12 months. 9 e-discharges were for Medical Outliers. These were excluded. 32 discharges from MC were to: nursing home (44%), home (38%), acute ward (9%), hospice (6%), and interim placement (3%). 4 discharges had no e-discharge summary. Of 28 patients with summaries: Patient GSF-code was recorded 36% summaries; resuscitation status 43%; present/absent EOLC medications 61%; inpatient ACP discussions 54%; TEP 50%. All five elements of G.R.E.A.T. present in only 25% of e-discharge summaries. Conclusion: A quarter of e-discharge summaries on patients within the last 12 months of life, did not include any information regarding G.R.E.A.T. Junior doctors can be supported in this respect.